Analyzing the Impact of Severe Tropical Cyclone Yasi on Public Health Infrastructure and the Management of Noncommunicable Diseases. Issue 1 (29th December 2014) - Ryan, Benjamin J.; Franklin, Richard C.; Burkle, Frederick M.; Watt, Kerrianne; Aitken, Peter; Smith, Erin C.; Leggat, Peter
Abstract: Introduction: Traditionally, post disaster response activities have focused on immediate trauma and communicable diseases. In developed countries such as Australia, the post disaster risk for communicable disease is low. However, a "disease transition" is now recognized at the population level where noncommunicable diseases (NCDs) are increasingly documented as a post disaster issue. This potentially places an extra burden on health care resources and may have implications for disaster-management systems. With increasing likelihood of major disasters for all sectors of global society, there is a need to ensure that health systems, including public health infrastructure (PHI), can respond properly. Problem: There is limited peer-reviewed literature on the impact of disasters on NCDs. Research is required to better determine both the impact of NCDs post disaster and their impact on PHI and disaster-management systems. Methods: A literature review was used to collect and analyze data on the impact of the index case event, Australia's Severe Tropical Cyclone Yasi (STC Yasi), on PHI and the management of NCDs. The findings were compared with data from other world cyclone events. The databases searched were MEDLINE, CINAHL, Google Scholar, and Google. The date range for the STC Yasi search was January 26, 2011 through May 2, 2013. No time limits were applied to the search from other cyclone events. The variables compared were tropical cyclones and their impacts on PHI and NCDs. The outcome of interest was to identify if there were trends across similar world events and to determine if this could be extrapolated for future crises. Results: This research showed a tropical cyclone (including a hurricane and typhoon) can impact PHI, for instance, equipment (oxygen, syringes, and medications), services (treatment and care), and clean water availability/access that would impact both the treatment and management of NCDs. The comparison between STC Yasi and worldwide tropical cyclones found the challenges faced were linked closely. These relate to communication, equipment and services, evacuation, medication, planning, and water supplies. Conclusion: This research demonstrated that a negative trend pattern existed between the impact of STC Yasi and other similar world cyclone events on PHI and the management of NCDs. This research provides an insight for disaster planners to address concerns of people with NCDs. While further research is needed, this study provides an understanding of areas for improvement, specifically enhancing protective PHI and the development of strategies for maintaining treatment and alternative care options, such as maintaining safe water for dialysis patients. BJ Ryan, RC Franklin, FM Burkle Jr, K Watt, P Aitken, EC Smith, P Leggat .Analyzing the impact of Severe Tropical Cyclone Yasi on public health infrastructure and the management of noncommunicable diseases .Prehosp Disaster Med .2015 ;30 (1 ):1 -10 .